A High Transconductance Accumulation Mode Electrochemical Transistor. (13th October 2014) - Inal, Sahika; Rivnay, Jonathan; Leleux, Pierre; Ferro, Marc; Ramuz, Marc; Brendel, Johannes C.; Schmidt, Martina M.; Thelakkat, Mukundan; Malliaras, George G.
<x xml:space="preserve">Abstract</x> An organic electrochemical transistor operates in accumulation mode with high transconductance. The channel comprises a thiophene‐based conjugated polyelectrolyte, which is p‐type doped by anions injected from a liquid electrolyte upon the application of a gate voltage. The use of ethylene glycol as a co‐solvent dramatically improves the transconductance and the temporal response of the transistors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>